The Influence of Vlogger’s Attributes on Travel Intention of Travel Vlog Followers in Bangkok Metropolitan Region - kunkojorn, kanyakan; Lekcharoen , Somchai (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
The objectives of this research were 1) to develop and validate the consistency of a causal relationship modal of followers’ travel intention on Travel Vlog in Bangkok Metropolitan Region and 2) to study the causal factors influencing followers’ travel intention on Travel Vlog in Bangkok Metropolitan Region. The tool used in the research was online questionnaires. The sample of this research consisted of 277 people who have been followed on Cultural Tourism Vlog and lived in Bangkok Metropolitan Region. The statistics used in data analysis were frequency, percentage, and structural equation modeling was used to analyze causal relationships to find the path to the causal influence of the variables consisting of 4 components including 1) Vlogger’s Attributes 2) Content Sharing Intention 3) Attitude toward Tourist Attractions 4) Travel Intention. The results of the research showed that the causal relationship model was developed in accordance with empirical data and considered by CMIN/df = 1.12, GFI = 0.93, AGFI = 0.91, CFI = 0.99, RMSEA = 0.02, SRMR = 0.03, RMR = 0.04, and the predictive coefficient = 0.85. Therefore, the variables in the model can explain the variance of followers’ travel intention on Travel Vlog by 85 percent. Attitude toward Tourist Attractions factor has the most direct influence on Travel Intention, and Vlogger’s Attributes has the most indirect influence on Travel Intention of followers on Travel Vlog.